Arabic Speaker Identification System for Forensic Authentication Using K-NN Algorithm - Abdulwahid S.; Mahmoud M.A.; Abdulwahid N. (Springer Science and Business Media Deutschland GmbH, 2023)
Classification (of information); Data mining; Digital forensics; Forestry; Learning algorithms; Loudspeakers; Motion compensation; Nearest neighbor search; Speech recognition; Trees (mathematics); K-near neighbor; Logistic model tree; Logistics model; Mel frequency cepstral co-efficient; Mel frequency cepstral coefficient; Mel-frequency cepstral coefficients; Mining classification; Model trees; Nearest-neighbour; Speaker identification systems; Authentication